In vitro testing of emulgel with a combined extract of Sansevieria trifasciata Prain. and Curcuma longa Linn. against the Candida albicans - Uswatun Chasanah; Ayudya Rizky Permatasari (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2020)
Content of flavonoids in Sansevieria trifasciata Prain. and curcumonoids in Curcuma Longa Linn. can inhibit the growth of the fungi Candida albicans in the wound. An innovative formulation was made that form a combination of antifungal extracts S. trifasciata and C. longa in the form of emulgel, which is easy to absorb and can moisturize the skin. The purpose is to determine the effect of antifungal activity of emulgel preparations using S. trifasciata extract with a concentration of 0%; 5%; and 10%, and C. longa 10% against C. albicans. S. trifasciata and C. longa extracts are formulated into emulgel in three formulas, F1 (C. longa 10%); F2 (S. trifasciata 5%; C. Longa 10%); and F3 (S. trifasciata 10%; C. Longa 10%). Antifungal activity was tested using the diffusion well method. The results of antifungal activity research showed inhibition zone diameter, inhibitory activity, and effectiveness. There were no significant differences in formula 1, formula 2, formula 3, but there were significant differences with positive controls. Variation the concentration of S. trifasciata 5% and 10% has no significant effect on the inhibitory zone of the C. albicans, but the three emulgel of S. trifasciata and C. Longa extract had antifungal activity on the growth of C. albicans.